2015
DOI: 10.1371/journal.pone.0128007
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Exposure to Hypoxia Is Sufficient to Induce CNS Dysmyelination, Modulate Spinal Motor Neuron Composition, and Impair Motor Development in Neonatal Mice

Abstract: Neonatal white matter injury (nWMI) is an increasingly common cause of cerebral palsy that results predominantly from hypoxic injury to progenitor cells including those of the oligodendrocyte lineage. Existing mouse models of nWMI utilize prolonged periods of hypoxia during the neonatal period, require complex cross-fostering and exhibit poor growth and high mortality rates. Abnormal CNS myelin composition serves as the major explanation for persistent neuro-motor deficits. Here we developed a simplified model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…16 A very recent report has shown that postnatal hypoxia significantly stunts growth and negatively modulates motor function. 35 Taken together, these studies point toward possible disease mechanisms.…”
Section: Skeletal Muscle Capillary Beds Fail To Develop Normally In Tmentioning
confidence: 89%
“…16 A very recent report has shown that postnatal hypoxia significantly stunts growth and negatively modulates motor function. 35 Taken together, these studies point toward possible disease mechanisms.…”
Section: Skeletal Muscle Capillary Beds Fail To Develop Normally In Tmentioning
confidence: 89%
“…The aetiology of the brain injuries leading to CP varies and is multi-factorial, and it includes hypoxia-ischaemia (HI), infection and inflammation, and affects different brain areas depending on the age of the foetus/infant [14, 15]. Several animal models of CP have been suggested, including the well-known hypoxic-ischaemic Rice-Vannucci model [1618]; various inflammation models (mimicking early infection), which mostly use the lipopolysaccharide (LPS; one of the major components of Gram-negative bacterial cell wall), or the interleukin 1b (IL1b) cytokine as inflammatory agents [19–23]; models that use hypoxia alone [24]; a combination of inflammation and HI [2528]; and a combination of inflammation and hypoxia [29, 30]. In the majority of the studies, inflammation was induced prenatally, either alone [22] or in combination with HI postnatally [26, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Using expression of transcription factors allows for an unambiguous identification of stages of oligodendrocyte development. Moreover, by using a milder form of hypoxia, such as in our model averts the presence of other cellular and molecular confounders seen in more severe injuries, such as necrosis and inflammation, that are normally present following hypoxia-ischemia (Rice et al, 1981;Vannucci, 1990) and more severe forms of global hypoxic injury, or a combination of the two (Back et al, 2002;Brazel et al, 2004;Segovia et al, 2008;van der Kooij et al, 2009;Watzlawik et al, 2015).…”
Section: Discussionmentioning
confidence: 99%